2019
DOI: 10.1021/acs.joc.9b01128
|View full text |Cite
|
Sign up to set email alerts
|

Regio- and Diastereoselective Access to 4-Imidazolidinones via an Aza-Mannich Initiated Cyclization of Sulfamate-Derived Cyclic Imines with α-Halo Hydroxamates

Abstract: An efficient regio-and diastereoselective cyclization of sulfamate-derived cyclic imines with unsubstituted or monosubstituted α-halo hydroxamates is developed under mild conditions. This reaction proceeds smoothly under transitionmetal-free conditions via a domino aza-Mannich addition/intramolecular nucleophilic substitution sequence, providing a convenient route to access 2-monosubstituted and 2,5-disubstituted 4-imidazolidinones. Notably, the products were obtained with single trans-isomers in moderate to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…The sequence is initiated by the aza‐Michael reaction between acrylamides 1 and Michael acceptors 6 that would be promoted (initiation step) by deprotonation of 1 by K 2 CO 3 to give the corresponding potassium amide. However, a competitive assisted aza‐Michael addition (concerted NH deprotonation‐N addition process) is also plausible . The resulting aza‐Michael adduct 8 then undergoes an intramolecular Michael addition leading to the enolate intermediate 9 , which finally reacts as a base to promote the formation of 8 (propagation step) with the concomitant release of the domino products 7 .…”
Section: Resultsmentioning
confidence: 99%
“…The sequence is initiated by the aza‐Michael reaction between acrylamides 1 and Michael acceptors 6 that would be promoted (initiation step) by deprotonation of 1 by K 2 CO 3 to give the corresponding potassium amide. However, a competitive assisted aza‐Michael addition (concerted NH deprotonation‐N addition process) is also plausible . The resulting aza‐Michael adduct 8 then undergoes an intramolecular Michael addition leading to the enolate intermediate 9 , which finally reacts as a base to promote the formation of 8 (propagation step) with the concomitant release of the domino products 7 .…”
Section: Resultsmentioning
confidence: 99%
“…[20] It is apparent that cis-configuration is introduced between methyl group on the 4-imidazolidinone and carboxylate in the diagram of 3 ai. On the basis of the above results and Chen's report, [19] we proposed a cascade aza-Mannich addition/intramolecular S N 2 pathway, as illustrated in Scheme 1. Under the promotion of base, the deprotonation on the nitrogen atom of α-bromo hydroxamates 2 and the simutaneous aza-Mannich addition to imines 1 could occur to produce intermediate A, followed by intramolecular S N 2 attack leading to 4-imidazolidinones 3.…”
mentioning
confidence: 73%
“…Owing to the significance of 4‐imidazolidinones as core skeletons of potentially bioactive compounds, the development of efficient and facile methods for their preparation are greatly valuable and, as a result, a challenging goal in the area of organic synthesis. In 2019, the reaction of α‐halogenated hydroxamates and sulfamate‐derived cyclic imines was successfully realized by Chen's group, [19] providing 2‐monosubstituted or 2, 5‐disubstituted 4‐imidazolidinones. This is the first successful example of preparing 4‐imidazolidinones directly using α‐halogenated hydroxamates.…”
Section: Figurementioning
confidence: 99%
“…α-Haloamides 2 were synthesized employing a literature procedure. 18 The Synthesis of N-tosyl-N-aryl Cyanamides 1. According to reported methods, 22 the aqueous solution of NaOCN (40 mmol, 30 mL) was added into a solution of ArNH 2 in acetic acid (20 mmol, 30 mL) with continuous stirring at room temperature.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…On the other hand, N -alkoxy α-haloamides have emerged as attractive reactants in [3 + m ] cycloadditions for the synthesis of various nitrogen-containing heterocycles . Our previous work clearly demonstrated that N -alkoxy α-haloamides could undergo [3 + 2] annulation via a tandem addition/intramolecular S N 2 cyclization procedure . Driven by our strong interest in developing efficient cycloaddition protocols to construct nitrogen-containing heterocycles, we conceived that NCTS and α-haloamides could undergo a cascade S N 2/5- exo -dig cyclization sequence, building two new C–N bonds and leading to five-membered cyclic guanidines (Scheme B, eq 4).…”
Section: Introductionmentioning
confidence: 99%